2011
DOI: 10.3748/wjg.v17.i21.2592
|View full text |Cite
|
Sign up to set email alerts
|

Current status of endoscopic submucosal dissection for the management of early gastric cancer: A Korean perspective

Abstract: The early diagnosis of gastric cancer allows patients and physicians to pursue the option of endoscopic resection, which is significantly less invasive than conventional surgical resection. In Korea, the use of endoscopic submucosal dissection (ESD) has been increasing, and many reports on ESD have been published. In addition, Korean gastroenterologists from several hospitals performing ESD have conducted formal meetings to discuss useful information regarding ESD. Here, we discuss the Korean experience with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Moreover, much time to hemostasis was observed in 16.9% of the cases. Complications involving perforation occurred in 2.3% and delayed bleeding in 3% of cases, comparable to results that have been reported elsewhere (Table 1) [1, 2, 1719]. …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, much time to hemostasis was observed in 16.9% of the cases. Complications involving perforation occurred in 2.3% and delayed bleeding in 3% of cases, comparable to results that have been reported elsewhere (Table 1) [1, 2, 1719]. …”
Section: Resultssupporting
confidence: 89%
“…Complications involving perforation occurred in 2.3% and delayed bleeding in 3% of cases, comparable to results that have been reported elsewhere (Table 1) [1, 2, 1719]. However, our hospital is a specialized center for ESD; many cases including lesions with high difficulty and high complications have been treated at our hospital.…”
Section: Discussionsupporting
confidence: 87%
“…Negative aspects of the remaining gastric mucosa include more local occurrence of metachronous gastric cancers in the ESD group compared to that in the surgical resection group. This is because the remaining gastric mucosa in the stomach has glandular atrophy or intestinal metaplasia with inflammation [15]. In this study, ESD group showed a higher rate of metachronous gastric cancer compared to the surgical resection group (6.2 vs 0.7 %).…”
Section: Discussionmentioning
confidence: 56%
“…ESD has become a popular treatment for selected EGC patients who met the absolute and expanded criteria in South Korea [15]. However, between 2006 and 2008, ESD was not well accepted among surgeons in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, most early gastric tumours do not present lymph node metastasis. Lymphatic involvement, tumour size and depth of submucosal invasion are prognostic factors [ 6 ], making the curative treatment of these lesions possible by endoscopy [ 24 ].…”
Section: Methodsmentioning
confidence: 99%